(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
Sports physician and trainers must be at their toe-tip to plan and provide safety medical measures and to limit injury at the site of practice. Every year, a small number of athletes die from cardiovascular problems. Sudden cardiac death represents perhaps the most tragic event seen in an athletic setting, particularly because the victim generally is a seemingly healthy, young athlete. This article focuses on several medical issues that can result in death of the athlete and therefore the potential for medicolegal action against the healthcare team. Regarding medical conditions of the athlete, special emphasis will be focused on cardiovascular and neurological manifestations.